Electrospun polyacrylonitrile–lauric acid composite nanofiber webs as a thermal energy storage material. (January 2019) - Ismar, Ezgi; Sarac, A Sezai
Phase-change materials have remarkable characteristics due to their simple phase-changeable nature. Within a certain temperature range, these materials can easily change from solid phase to liquid phase or vice versa. It is possible to build thermal energy storage mechanisms, thanks to their latent heat. In this study, composite nanofiber structures were prepared with lauric acid and polyacrylonitrile blends. Nanofiber webs were fabricated via electrospinning technique and combined with phase-change material due to their light weight and high surface area. Thermal energy storage properties were investigated via differential scanning calorimeter, and structural analysis was studied by Fourier transform infrared–attenuated total reflection spectroscopy. Scanning electron microscope was used to investigate the surface morphology of the fibers. Blended polyacrylonitrile–lauric acid nanofibers were successfully converted to nanofiber formation without losing their properties. Results showed that fabricated polyacrylonitrile–lauric acid composite nanofiber webs can be used as a thermal energy storage patch.